Measuring the degree of connection between currency futures: Empirical dive into higher moments - Donduran, Murat; Faisal, Muhammad Ali (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeThe purpose of this study is to unfold the existing information channel in the higher moments of currency futures for different time horizons.Design/methodology/approachThe authors use a quasi-Bayesian local likelihood approach within a time-varying parameter vector autoregression (TVP-VAR) framework and a dynamic connectedness measure to study the volatility, skewness and kurtosis of most traded currency futures.FindingsThe authors' results suggest a time-varying presence of dynamic connectedness within higher moments of currency futures. Most spillovers pertain to shorter time horizons. The authors find that in net terms, CHF, EUR and JPY are the most important contributors to the system, while the authors emphasize that the role of being a transmitter or a receiver varies for pairwise interactions and time windows.Originality/valueTo the best of the authors' knowledge, this is the first study that looks upon the connectivity vis-a-vis uncertainty, asymmetry and fat tails in currency futures within a dynamic Bayesian paradigm. The authors extend the current literature by proposing new insights into asset distributions.
Keywords: Currency futures; TVP-VAR; Volatility; Skewness; Kurtosis; C49; F31; G15; IMPULSE-RESPONSE ANALYSIS; VOLATILITY SPILLOVERS; PRICE DISCOVERY; CONNECTEDNESS; MARKETS; RETURN; RISK; Business & Economics